Examining Text Environments in Elementary Chilean Classrooms. Issue 2 (2nd April 2016) - Orellana-Garcia, Pelusa; Sailors, Misty
ABSTRACT: In this study, we examine the social practices related to literacy in classrooms in Chile in order to examine school-based literacy practices. We also examined the constraints and affordances literacy learning offered Chilean students. Through our case study and cross-case analysis, we discovered that although the classrooms contained an assortment of materials, they only offered an "adequate" amount and quality of texts; there were very few local texts. There were differences in the understanding and valuing of texts by students of differing reading abilities. Our research has implications for teacher professional development and teacher education, as well as future research endeavors.